2004
DOI: 10.1080/10588330490519428
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Depleted Uranium Sorption and Solubility with Depth in Arid Soils

Abstract: This study examined the ability of alkaline desert soils to sorb depleted uranium (DU) as a function of soil horizon and assessed the solubility of corrosion and migration products from two DU kinetic energy penetrators exposed on the desert surface for a 22-y period. Both uranium corrosion products on the surface, and subsurface uranium originating from the dissolution of surface corrosion products followed by reprecipitation or sorption, were examined. A four-step sequential extraction method was used to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 11 publications
5
39
3
Order By: Relevance
“…Johnson et al [15] reported 29-52% DU in the residuals fraction of their sequential extraction tests. Coatings of amorphous silica around schoepite particles and aggregates with clays and calcium carbonate were found to inhibit U solubility during extraction experiments and cause it to be recovered in the residual phase.…”
Section: Sequential Extraction Of Contaminated Finesmentioning
confidence: 98%
See 2 more Smart Citations
“…Johnson et al [15] reported 29-52% DU in the residuals fraction of their sequential extraction tests. Coatings of amorphous silica around schoepite particles and aggregates with clays and calcium carbonate were found to inhibit U solubility during extraction experiments and cause it to be recovered in the residual phase.…”
Section: Sequential Extraction Of Contaminated Finesmentioning
confidence: 98%
“…Sequential analysis of the upper 4 cm of the soil profile showed that at least half of the total DU may be attributed to the carbonate fraction (Stage 2 of the sequential extraction). The relative ease of DU dissolution implied that uranyl hydroxide minerals were present [15]. No DU was in the exchangeable fraction for the first 8 cm below the surface.…”
Section: Sequential Extraction Of Contaminated Finesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, U 4 O 9 , U 3 O 7 and UO 3 have also been reported from DU penetrator tests (Chazel et al, 2003). Fragments and particles are also formed as unspent DU penetrators deposited in the field will corrode over time due to oxidation of the metal Johnson et al, 2004;Mellini and Riccobono, 2005;Salbu et al, 2005). In the environment, U metal can also experience passivation where an oxide, hydroxide or salt coating can protect against further corrosion.…”
Section: Introductionmentioning
confidence: 94%
“…Depleted uranium can undergo a variety of transitions from dissolution of surface corrosion products, followed by re-precipitation and sorption through the formation of insoluble aggregates with minerals [11].…”
mentioning
confidence: 99%